Intravenous thrombolysis for acute ischemic stroke in Asia. (February 2012) - Sharma, Vijay K; Ng, Kay WP; Venketasubramanian, Narayanaswamy; Teoh, Hock L; Chan, Bernard PL
Data regarding thrombolysis for acute ischemic stroke in Asia are scarce and only a small percentage of patients are thrombolysed. Clinical trials that led to the recommended dose of intravenously administered tissue plasminogen activator (IV-tPA) included predominantly Caucasian patients. However, the single-arm case-controlled observational studies in Japanese patients suggested the clinical efficacy and safety of low-dose IV-tPA (0.6 mg/kg bodyweight; maximum 60 mg) comparable with standard dose (0.9 mg/kg bodyweight; maximum 90 mg). There has been no randomized clinical trial for determining the dose, efficacy or safety of IV-tPA in Asia. Accordingly, the dose of IV-tPA in Asia remains controversial. Reduced treatment cost, lower symptomatic intracerebral hemorrhage risk and comparable efficacy encouraged many Asian centers to adopt low-dose or even variable-dose IV-tPA regimens. We present the current status of thrombolysis for acute ischemic stroke in Asia.